Пошаговое объяснение
х^4+х^2+1=0
t=х^2
t^2+t+1=0
d=1-4=-3
t1=(-1+i*корень(3))/2 =-1/2+i*корень(3)/2=-cos(pi/3)+i*sin(pi/3)=cos(2pi/3)+i*sin(2pi/3)
t2=(-1-i*корень(3))/2 =-1/2-i*корень(3)/2=-cos(pi/3)-i*sin(pi/3)=cos(4pi/3)+i*sin(4pi/3)
x1=cos(pi/3)+i*sin(pi/3) - первый корень уравнения x^2=cos(2pi/3)+i*sin(2pi/3)
x2=cos(4pi/3)+i*sin(4pi/3)- второй корень уравнения x^2=cos(2pi/3)+i*sin(2pi/3)
x3=cos(2pi/3)+i*sin(2pi/3) - первый корень уравнения x^2=cos(4pi/3)+i*sin(4pi/3)
x4=cos(5pi/3)+i*sin(5pi/3)- второй корень уравнения x^2=cos(4pi/3)+i*sin(4pi/3)
имеем 4 комплексных корня в тригонометрическом виде
2/11(*4) +7/22(*2) +5 2/44=4/44+14/44+5 2/44=18/44+5 2/44=5 20/44=5 5/11
25/49(*2) -1/7(*14) -5/14(*7)=50/98-14/98-35/98=1/98
9,05-4 3/5=905/100-4 3/5=905/100-23/5(*5)=905/100-115/100=790/100=
=7 90/100= 7 9/10
47 7/8(*4) -45 15/32=47 28/32-45 15/32=2 13/32